Bank selection and customers' perception of banks in Malaysia - Ismail, Norhazlin; Selamat, Zarehan; Ong, Hway-Boon (2004)
The process customers go through in choosing a bank has been studied for several decades using different approaches. Understanding the needs and analyzing how the customers select their banks are crucial steps towards the improvement of customer satisfaction. In this study, an attempt is made to identify the determinants of bank selection and customers' perception of banks in Malaysia.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 122)
Keywords: Banks and banking -- Malaysia; Consumer satisfaction -- Malaysia